11.0k views
1 vote
Raise the quality in parentheses to the indicated exponent, and slim lift the resulting expression with positive exponents.

Raise the quality in parentheses to the indicated exponent, and slim lift the resulting-example-1
User Nitneq
by
5.9k points

1 Answer

0 votes

For this case we have the following expression:


(\frac {-27x ^ 0 * y ^ {- 2}} {54x ^ {- 5} * y ^ {- 4}}) ^ {- 2} =

By definition we have to:


a^0= 1

So:


(\frac {-27y ^ {- 2}} {54x ^ {- 5} * y ^ {- 4}}) ^ {- 2} =

Simplifying:


(\frac {-y ^ {- 2}} {2x ^ {- 5} * y ^ {- 4}}) ^ {- 2} =

By definition of power properties we have to:


(a ^ n) ^ m = a ^ {n * m}

So, rewriting the expression we have:


\frac {-y ^ {- 2 * -2}} {4x ^ {- 5 * -2} * y ^ {- 4 * -2}} =\\\frac {-y ^ {4}} {4x ^ {10} * y ^ {8}} =

SImplifying:


\frac {-y ^ {4-8}} {4x ^ {10}} =\\\frac {-y ^ {- 4}} {4x ^ {10}} =\\- \frac {1} {4x ^ {10} y^ {4}}

Answer:


- \frac {1} {4x ^ {10} y ^ {4}}

User Rhettg
by
5.8k points